2003
DOI: 10.1103/physrevlett.90.151101
|View full text |Cite
|
Sign up to set email alerts
|

New Experimental Constraints on Non-Newtonian Forces below100μm

Abstract: We have searched for large deviations from Newtonian gravity by means of a finite-frequency microcantilever-based experiment. Our data eliminate from consideration mechanisms of deviation that posit strengths approximately 10(4) times Newtonian gravity at length scales of 20 microm. This measurement is 3 orders of magnitude more sensitive than others that provide constraints at similar length scales.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
208
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(218 citation statements)
references
References 13 publications
8
208
2
Order By: Relevance
“…Testing the existence of branes or extra dimensions is therefore becoming a fundamental challenge. Such evidences are expected to be obtained through high energy collisions [2][3][4], but it has been also demonstrated that some detectable effects could also be observed at low energy [2,3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . This is the topic of the present paper.…”
Section: Introductionmentioning
confidence: 93%
“…Testing the existence of branes or extra dimensions is therefore becoming a fundamental challenge. Such evidences are expected to be obtained through high energy collisions [2][3][4], but it has been also demonstrated that some detectable effects could also be observed at low energy [2,3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] . This is the topic of the present paper.…”
Section: Introductionmentioning
confidence: 93%
“…We have used static AFM techniques to measure the mentioned force between the sphere and a metal coated plate [7]. The dynamical AFM (DAFM) technique which measures the force gradient between the sphere and substrate is expected to be more sensitive [9][10][11][12][13]. More sensitivity implies higher precision in the Casimir force measurements at the explored sphere to plate distances.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental groups have utilized this recipe to measure the spin of small ensembles of electrons or nuclei [12]. Researchers have also used these types of cantilevers to make noncontact friction measurements [11], and non-Newtonian force measurements [13]. These experiments were mostly done with cantilevers fabricated in a traditional nanofabrication facility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional experiments, following the pioneering measurements of Cavendish in 1798 [125], now use a variety of approaches from superconducting gravity gradiometers [126] and microcantilevers [127] to planar oscillators [128] and torsion balance experiments [129]. However, in scaling down experiments to probe ever decreasing length scales a new, fundamental problem arises.…”
Section: Soliton Surface Probes and Quantum Reflectionmentioning
confidence: 99%